Future projections of extreme climatic events over Iberian Peninsula - Vaz, Susana Cardoso Pereira Firmino (2020)
In recent years, several extreme events had given the awareness that our climate has become more extreme. Extreme events, due to their nature, have a high disruptive potential, so society has more difficulty in accommodating its change, becoming more vulnerable to the occurrence of this type of change, than to a gradual change in the mean climate conditions. This study is interested in events related to temperature and precipitation, on a regional scale, because these climate parameters play a significant role in the Iberian Peninsula, a vulnerable and susceptible region to changes in temperature and precipitation. Throughout this study, several basic statistical metrics were used, such as daily or seasonal totals, mean, deviations to the mean state (anomalies), nonparametric probability distribution (PDF) functions, and percentile calculation. In the case of precipitation, the climatic simulations were corrected concerning bias. The application of a bias correction method, namely, the quantile mapping, reduced the systematic errors present in models’ simulations. This study uses a specific methodology of bias correction to correct systematic bias, presented as a novel bias correction methodology for climate modelling simulations in the Iberian Peninsula. The concept of precipitation episode, as defined in this study, has a character of novelty. Precipitation episode is defined as a series of consecutive wet days. For each episode, the duration and intensity were calculated, i.e., the number of rainy days, and the average of the total precipitation, respectively. Then, the episodes were grouped into classes of intensity and duration. The heatwaves and cold spells were analysed with special attention to the summer and winter season, respectively. The main results project, towards the end of the 21st century, changes in the character of precipitation and precipitation episodes, and changes for temperature-related events. There is a reduction in annual precipitation and the seasonal precipitation for the spring to autumn months. An increase in precipitation is projected for the winter season. The winter episodes of short duration and lower intensity increase in the north and northwest regions of the Iberian Peninsula. The major findings project an increase in the maximum and minimum temperature and an increase in the number of heatwaves. Although in none of the variables there is a change in its seasonal structure, some results suggest an increase in the number of hot to very hot summer days, which can extend the summer season. Current extreme events will be the norm of the future. The end of the 21st century, in the Iberian Peninsula, is projected to be drier and warmer.